2009
DOI: 10.1371/journal.pntd.0000452
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Cestode Echinococcus multilocularis in Red Foxes at a Continental Scale in Europe

Abstract: BackgroundAlveolar echinococcosis (AE) is a severe helminth disease affecting humans, which is caused by the fox tapeworm Echinococcus multilocularis. AE represents a serious public health issue in larger regions of China, Siberia, and other regions in Asia. In Europe, a significant increase in prevalence since the 1990s is not only affecting the historically documented endemic area north of the Alps but more recently also neighbouring regions previously not known to be endemic. The genetic diversity of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 26 publications
5
81
1
11
Order By: Relevance
“…Genetically different E. multilocularis worms were found in in 38% of 13 foxes in Hokkaido, Japan (Nakao et al, 2003), 52% of 25 foxes in France (Knapp et al, 2008) and 35% of 125 foxes throughout Europe (Knapp et al, 2009), while genetically different E. granulosus worms were found in 50% of dogs in Argentina (Haag et al, 2011). These data suggest that it is not unusual for definitive hosts to be infected with genetically different worms of the same species.…”
Section: The Interesting Question Ismentioning
confidence: 83%
See 2 more Smart Citations
“…Genetically different E. multilocularis worms were found in in 38% of 13 foxes in Hokkaido, Japan (Nakao et al, 2003), 52% of 25 foxes in France (Knapp et al, 2008) and 35% of 125 foxes throughout Europe (Knapp et al, 2009), while genetically different E. granulosus worms were found in 50% of dogs in Argentina (Haag et al, 2011). These data suggest that it is not unusual for definitive hosts to be infected with genetically different worms of the same species.…”
Section: The Interesting Question Ismentioning
confidence: 83%
“…There have been far fewer studies on other species, but Knapp et al (2009) found microsatellite allelic diversity in E. multilocularis in Europe to be greatest in historically endemic areas centred on Switzerland and lower in northern and eastern regions where the parasite has only been recently recorded. Nakao et al (2010b) found low levels of mtDNA diversity in E. multilocularis in the Tibetan Plateau and suggested that the species was introduced to this region by a recent range extension of the red fox (Vulpes vulpes), although this hypothesis requires confirmation because there does not seem to be independent evidence of such a range extension (Kutschera et al, 2013).…”
Section: Genetic Diversity Within Populations Reflects Time Since Colmentioning
confidence: 99%
See 1 more Smart Citation
“…Knapp et al (2009a) studied the genetic diversity of E. multilocularis in Europe using the microsatelite marker EmsB in association with matching the fox hosts geographical positions. A central core of the European focus was identified in Switzerland and the Swabian Jura (Germany) flanked by neighbouring regions where E. multilocularis exhibits a lower genetic diversity than that in the centre.…”
Section: Expansion or New Detection Of Endemic Areas?mentioning
confidence: 99%
“…Moreover, mathematical calculation based on two examinations of red foxes between 1996 and 2003 in the Netherlands showed that the parasite prevalence is increasing in number and is spreading northward at the speed of 2.7 km per year (29). Furthermore, the expansive character of E. multilocularis infection was confirmed and described based on the analysis of the genetic diversity of this species in France (16,30) and the whole Europe (15). In Europe, the increasing trend of E. multilocularis infection in red foxes is observed.…”
Section: Discussionmentioning
confidence: 88%